2000
DOI: 10.1067/mhn.2000.109759
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implant Performance in Senior Citizens

Abstract: Cochlear implants are indicated for elderly patients with severe-to-profound hearing loss (sensorineural hearing loss >/=70 dB). Their use has been limited, possibly by the misconception that elderly patients will perform poorly. To document the performance of older adults (> or =65 years old), we undertook a retrospective analysis of our postlingually deafened adult patients who underwent implantation with the CLARION Multi-Strategy Cochlear Implant and underwent formal audiologic analysis (sentence recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
92
4
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 13 publications
11
92
4
1
Order By: Relevance
“…We have used the SMA for CI in our department since 1999 [9] . Fourteen of the twenty elderly patients who were implanted after 1999 underwent their CI by means of this technique and the mean duration of surgery was 72 min (range 60-80 min) -this is in contrast to Chatelin et al [18] and Labadie et al [4] , who reported that CI surgery usually required general anesthesia for approximately 3-4 h. In our experience, the SMA can cut this time by half, an advantage especially beneficial in a geriatric population.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…We have used the SMA for CI in our department since 1999 [9] . Fourteen of the twenty elderly patients who were implanted after 1999 underwent their CI by means of this technique and the mean duration of surgery was 72 min (range 60-80 min) -this is in contrast to Chatelin et al [18] and Labadie et al [4] , who reported that CI surgery usually required general anesthesia for approximately 3-4 h. In our experience, the SMA can cut this time by half, an advantage especially beneficial in a geriatric population.…”
Section: Discussioncontrasting
confidence: 47%
“…Bypassing the cochlea by means of cochlear implantation (CI) not only provides considerable benefit for this population [1] but is cost effective as well [2] . It is well established by now that CI provides similar improvement in subjective quality of life and audiological benefit both in elderly and young adults [1,[3][4][5][6][7] . Elderly recipients demonstrated no difference in hours per day of implant usage, ability to discriminate environmental sounds from human voices, or ability to telephone communication compared to younger CI users [1] .…”
mentioning
confidence: 99%
“…Cochlear implantation carries minimal risk and has been proven to be a safe procedure in all age groups (Venail et al, 2008) including the older population (Budenz et al, 2011;Carlson et al, 2010;Chatelin et al, 2004;Coelho, Yeh, Kim, & Lalwani, 2009;Djalilian, King, Smith, & Levine, 2002;Eshraghi et al, 2009;Haensel, Ilgner, Chen, Thuerman, & Westhofen, 2005;Labadie, Carrasco, Gilmer, & Pillsbury, 2000;Orabi, Mawman, Al-Zoubi, Saeed, & Ramsden, 2006). These authors generally agree that older adults present with more comorbid conditions at the time of surgery, and the patient's preexisting medical conditions are more important for determining intra-or postoperative complications than age alone.…”
Section: Existing Studies Of Older CI Listenersmentioning
confidence: 80%
“…These authors generally agree that older adults present with more comorbid conditions at the time of surgery, and the patient's preexisting medical conditions are more important for determining intra-or postoperative complications than age alone. The outcomes of implantation in older adults are excellent such that speech understanding is significantly improved between preoperative and postoperative test intervals (Djalilian et al, 2002;Eshraghi et al, 2009;Haensel et al, 2005;Labadie et al, 2000;Migirov, Taitelbaum-Swead, Drendel, Hildesheimer, & Kronenberg, 2010;Orabi et al, 2006;Pasanisi et al, 2003;Shin et al, 2000). The benefits of improved audibility and speech recognition are expected to cascade into other areas of life such as the patient's social, psychological, and overall physical health.…”
Section: Existing Studies Of Older CI Listenersmentioning
confidence: 90%
See 1 more Smart Citation